2022
DOI: 10.1056/nejmoa2119451
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Vaccine Effectiveness against the Omicron (B.1.1.529) Variant

Abstract: Background A rapid increase in coronavirus disease 2019 (Covid-19) cases due to the omicron (B.1.1.529) variant of severe acute respiratory syndrome coronavirus 2 in highly vaccinated populations has aroused concerns about the effectiveness of current vaccines. Methods We used a test-negative case–control design to estimate vaccine effectiveness against symptomatic disease caused by the omicron and delta (B.1.617.2) variants in England. Vaccine effectiveness was calcula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

158
1,983
11
12

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 2,070 publications
(2,164 citation statements)
references
References 24 publications
158
1,983
11
12
Order By: Relevance
“…We find evidence of moderate reductions in the protection vaccines provide against hospitalisation in breakthrough omicron cases compared with that of delta, and previous studies indicate substantial reductions in vaccine effectiveness against symptomatic infection. 18 However, we find that receiving an mRNA vaccine booster dose gives over 70% protection against hospitalisation or mortality outcomes in breakthrough omicron cases; absolute vaccine effectiveness will be substantially higher once protection against infection is accounted for. 19…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…We find evidence of moderate reductions in the protection vaccines provide against hospitalisation in breakthrough omicron cases compared with that of delta, and previous studies indicate substantial reductions in vaccine effectiveness against symptomatic infection. 18 However, we find that receiving an mRNA vaccine booster dose gives over 70% protection against hospitalisation or mortality outcomes in breakthrough omicron cases; absolute vaccine effectiveness will be substantially higher once protection against infection is accounted for. 19…”
Section: Discussionmentioning
confidence: 74%
“…In vaccinated cases, past infection offered no additional protection against hospitalisation over vaccination alone, but did offer moderate additional protection against death. 18 An imputation-based sensitivity analysis to examine the effect of under-ascertainment of past infections gave slightly higher estimates of the severity of omicron relative to delta, together with estimates indicating a larger protective effect of past infection against all endpoints for unvaccinated individuals, and against hospital admission and death in vaccinated individuals. 8…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of the coronavac (Sinovac) vaccines have shown that they significantly protected against moderate and severe disease, hospitalisation, and deaths and moderately reduced incident cases [46]. A recently published test-negative case-control design to estimate vaccine effectiveness against symptomatic disease caused by the Omicron and Delta (B.1.617.2) variants in England showed that primary immunization with two doses of ChAdOx1 nCoV-19 or BNT162b2 vaccine provided limited protection against symptomatic disease caused by the Omicron variant [47]. The same study revealed that a BNT162b2 or mRNA-1273 booster after either the ChAdOx1 nCoV-19 or BNT162b2 primary course substantially increased protection but that protection waned over time [47].…”
Section: Implications Of Variants Of Concern On the Efficacy Of Curre...mentioning
confidence: 99%